2020
DOI: 10.3390/ijerph17062021
|View full text |Cite
|
Sign up to set email alerts
|

Older People’s Perception of Changes in Their Living Environment after Relocation: A Case Study in Beijing, China

Abstract: Beijing has been experiencing population ageing and rapid urbanization processes. Older people's living environment has changed dramatically. This research aims to understand the older people's perception of the changes in their living environment, the determinants of age-friendly living environment, and the impact path before and after their relocation in Beijing. The quantitative analysis is based on 353 valid questionnaires collected in four sample communities in Beijing. By using descriptive analysis and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Most studies found that urban or plain areas had higher spatial accessibility to health services than rural or mountainous areas. This spatial discrepancy could be attributed to fundamental differences in geography and economic and social development [57,71,72]. This study also indicated a gradient of community-hospital accessibility, gradually decreasing from the central urban area to the urban edge.…”
Section: Spatial Accessibility Factors Of Community Hospitalsmentioning
confidence: 74%
“…Most studies found that urban or plain areas had higher spatial accessibility to health services than rural or mountainous areas. This spatial discrepancy could be attributed to fundamental differences in geography and economic and social development [57,71,72]. This study also indicated a gradient of community-hospital accessibility, gradually decreasing from the central urban area to the urban edge.…”
Section: Spatial Accessibility Factors Of Community Hospitalsmentioning
confidence: 74%
“…Accessible recreational places play an important role in enhancing senior citizens' physical and mental health and improving their sense of happiness [43,44]. As the physical strength of senior citizens declines markedly with aging, their daily activity space tends to shrink gradually [45]. The spatial accessibility of different activity locations is a crucial factor influencing the daily outdoor participation of senior citizens [46].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, several studies report a significant association between social support and self-neglect in different countries ( Burnett et al, 2006 ; Dyer and Reyes-Ortiz, 2017 ). However, the implementation of the one child policy, changed family structures, and the large-scale migration of younger adults seeking employment has decreased the social support for older adults in China ( Cao et al, 2015 ; Zhong et al, 2018 ; Gao and Cheng, 2020 ). Therefore, there is an urgent need to find alternative solutions.…”
Section: Introductionmentioning
confidence: 99%